2002
DOI: 10.1002/j.2050-0416.2002.tb00544.x
|View full text |Cite
|
Sign up to set email alerts
|

A Reappraisal of the Differences Between Scandinavian and Spanish Barleys: Effect of β-Glucan Content and Degradation on Malt Extract Yield in the cv.Scarlett

Abstract: Forty one samples of the malting barley cultivar Scarlett were collected from both Scandinavia (15 from Finland and 10 from Denmark) and the Iberian Peninsula (15 from Spain and 1 from Portugal), during the harvest years of 1998 and 1999. These samples were subjected to grain analyses, comprising protein content, hordein fractions by high performance liquid chromatography (HPLC) and b-glucan content. The samples were micro-malted and the malts were analysed to determine different patterns in the influence of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 12 publications
1
8
0
2
Order By: Relevance
“…The effect of under modification on fermentability is not well understood even though it is often referred to in the literature 2,11,[13][14][15]22 . Results from the present study suggested several factors were involved in restricting fermentability.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of under modification on fermentability is not well understood even though it is often referred to in the literature 2,11,[13][14][15]22 . Results from the present study suggested several factors were involved in restricting fermentability.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies on Spanish-vs. Scottish-grown barleys 5,9,17 , South-European vs. North-European grown barleys [11][12][13] and Spanish-vs. Scandinavian-grown barleys [12][13][14] , the Spanish-grown barleys showed a higher capacity to develop degrading enzymes during germination, so circumventing their inherent high-protein drawback. In the present case, whereas BPT exerts a negative influence on Cana- dian FEX and CEX, it did not have a significant influence on these parameters in barley grown in Spain (Table IV).…”
Section: Discussionmentioning
confidence: 99%
“…Once a good malting variety is identified and its range of geographical adaptation defined, it emerges that the environmental influence (seasons and sites) on its final malting quality is of paramount importance, as shown by recent studies carried out to assess the different patterns of malt extract development in different European regions [11][12][13][14] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could again be influenced by the increased breakdown of β ‐glucan during germination, which may increase access for amylolitic enzymes to the endosperm. Also, hydrolysis of β ‐glucan yields glucose which adds to the fermentable sugars and increases fermentability . In conclusion, the overall quality of the worts from all malts was high and extending the period of germination did not negatively affect the results of our tests.…”
Section: Resultsmentioning
confidence: 67%